Transformation of Traditional Coffee Businesses into Techno-Entrepreneurship-Based Enterprises - Marpaung, Astrida Natalia; Lumbanbatu, Maristella J; Aldino, Reno; Halawa, Sernianti (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the transformation process of traditional coffee businesses into techno-entrepreneurship–based enterprises through the utilization of digital technology, strengthening of business models, and digitalization of marketing strategies. The research was conducted among coffee MSMEs in Huta Tinggi Village, Samosir Regency. The study employed a mixed-method approach (qualitative–quantitative) using observation, interviews, documentation, and pre–post test questionnaires as data collection techniques. The results indicate that technology-based business transformation increased the entrepreneurs’ digital literacy by 72%, expanded market reach, enhanced professionalism in business management, and contributed to an average sales increase of 22%. The implementation of techno entrepreneurship through digital marketing, marketplace utilization, branding, and simple financial record-keeping has proven to improve the competitiveness and sustainability of local coffee businesses.